1995
DOI: 10.1111/j.1432-1033.1995.tb20184.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Kinetic Constants for the Interaction Between the Platelet Glycoprotein IIb-IIIa and Fibrinogen by Means of Surface Plasmon Resonance

Abstract: The binding reaction between purified human platelet glycoprotein IIb-IIIa and fibrinogen was investigated by real-time measurements using the surface-plasmon-resonance sensor technology. In these experiments, either glycoprotein IIb-IIIa or fibrinogen was immobilized on a sensor surface. The time-dependent change in surface coverage that occurred immediately upon contact with a solution of the complementary protein was then detected. The ability to record this dynamic event from its initiation allowed the col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
29
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 42 publications
4
29
0
Order By: Relevance
“…These values are comparable with those determined by the same method for the interaction of integrins with their natural ligands such as between ␣ v ␤ 3 and osteopondin (K D ϭ 0.43 nM) (48), ␣ v ␤ 3 and the P1 fragment of laminin (K D ϭ 450 nM) (49), or ␣ IIb ␤ 3 and fibrinogen (K D ϭ 20 -70 nM) (50). For comparison, the affinity determined for the binding of the Fab-9 antibody to the ␣ IIb ␤ 3 integrin was also in the nanomolar range (51).…”
Section: Discussionsupporting
confidence: 81%
“…These values are comparable with those determined by the same method for the interaction of integrins with their natural ligands such as between ␣ v ␤ 3 and osteopondin (K D ϭ 0.43 nM) (48), ␣ v ␤ 3 and the P1 fragment of laminin (K D ϭ 450 nM) (49), or ␣ IIb ␤ 3 and fibrinogen (K D ϭ 20 -70 nM) (50). For comparison, the affinity determined for the binding of the Fab-9 antibody to the ␣ IIb ␤ 3 integrin was also in the nanomolar range (51).…”
Section: Discussionsupporting
confidence: 81%
“…Our experiments suggest that the bond off‐rate may not be influenced by the Leu33Pro polymorphism, since both the Leu33 and Pro33 cells that adhered on fibrinogen at 25 s −1 could not be dislodged even after increasing the shear rate up to 1000 s −1 at the end of the perfusion (data not shown). Studies using surface plasmon resonance spectroscopy suggest that α IIb β 3 –fibrinogen binding consists of two consecutive processes: an initial fast reaction, with a reversible low affinity complex and a subsequent slower high affinity complex [28]. It is plausible that the combined presence of shear and the β 3 ‐helix disrupting residue proline could change the kinetic rates (and increase the on‐rate) of integrin α IIb β 3 to fibrinogen at one or both these steps.…”
Section: Discussionsupporting
confidence: 57%
“…This apparent discrepancy is clearly alleviated if the arrests we detected reflected a transient binding state. Further, other studies made on noncovalent ligand-receptor interactions revealed such intermediate states (31)(32)(33). Therefore, our three-parameter model may be considered as the simplest 1 We are grateful to Prof. Evan Evans for pointing out the importance of the difference of the forces experienced by the sphere and the bond.…”
Section: The Distribution Of Arrest Durations Is Quantitatively Consimentioning
confidence: 70%